Prices of raw materials continue to rise - Heinz Kolbe (Intereconomics, 1983)
Following the abatement of the boom market during the early months of 1983, the coming months will see an “adjustment” of world market prices for industrial raw materials to “fundamental” market conditions. Price fluctuations are likely during this period. A gradual increase in demand for raw materials and a moderate rise in raw materials prices can be expected during the further course of 1983 and in 1984.
Keywords: 330; Economic Trends